Barbara M. Reul and Lorraine Byrne Bodley (eds), The Unknown Schubert (2008) (Journal of the Society for Musicology in Ireland, 2009)
A review of Barbara M. Reul and Lorraine Byrne Bodley (eds), The Unknown Schubert (Aldershot: Ashgate, 2008), ISBN 978-0-7546-6192-4